SITUATIONAL FACTORS SHAPING VIETNAMESE STUDENTS’ WILLINGNESS TO COMMUNICATE IN EFL SPEAKING CLASSROOMS - Trang Thu Nguyen (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
Students’ reluctance to speak in English as Foreign Language (EFL) classes poses a major challenge for teachers. This issue may stem from either learner-related characteristics (e.g., anxiety, confidence) or environmental factors (e.g., classroom climate, peer support). The current study explores Vietnamese students’ perceptions of situational variables affecting their willingness to communicate (WTC) in EFL speaking classrooms. Employing a qualitative research design, semi-structured interviews were conducted with ten third-year Vietnamese English-major students and analyzed using thematic analysis. The findings reveal that students’ WTC is influenced by multiple situational factors that can be categorized into task type, peer characteristics, and teacher practices. Specifically, students show greater WTC during interactive tasks such as games, videos, pair work, or small-group discussions on engaging topics. A supportive classroom climate and cooperative peers further enhance communicative readiness. Furthermore, teachers play a crucial role in fostering WTC through openness, approachability, and flexible pedagogy. The current study contributes to contextual understandings of WTC in EFL by highlighting situational factors specific to Vietnamese classrooms, thereby extending existing research beyond individual psychological variables. Pedagogical implications for designing interactive, supportive classroom environments that foster participation and communicative confidence are also offered.